The best of America's test kitchen. Best baking recipes [videorecording (DVD)] - Kimball, Christopher; Lancaster, Bridget; Ried, Adam (WGBH Boston Video, 2007)
Join Christopher Kimball and the cast of America's Test Kitchen to learn the basics of great home cooking. This special collection also includes independent reviews of indispensable kitchen equipment, and recommendations for supermarket staples from chocolate and white wine vinegar to inexpensive steaks and tomato paste.